EFFECTIVENESS OF THE PROJECT BASED LEARNING MODEL USED BY CANVA ON IMPROVING STUDENT CREATIVITY: ( Experimental Study of Grade XI Students of SMAN 11 Garut in the 2024-2025 Academic Year in Pancasila Education Learning) - Wina Fauziyah; Odang Hermanto; Prima Melati (Journal Civics And Social Studies, 2025)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) learning model assisted by Canva on increasing students' creativity in making posters in the Pancasila Education subject at SMAN 11 Garut. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group design. The study population was all students of grade XI, while the sample was determined through purposive sampling, namely class XI.10 as the experimental class and XI.4 as the control class with a total of 40 students each. The experimental class received PjBL learning assisted by Canva, while the control class used PjBL manually. Creativity data were collected through a creativity questionnaire and poster project assessment using a rubric. Data analysis included descriptive statistics, normality tests, paired sample t-tests, independent sample t-tests, and N-Gain calculations. The results showed that the average creativity of the experimental class increased from 66.23% to 80.62%, a 14.39% increase, while the control class only increased from 67.21% to 73.83%, a 6.62% increase. The average poster project score of the experimental class (91.09; highly creative category) was higher than that of the control class (77.66; creative category). Statistical tests and N-Gain showed that Canva-assisted PjBL was more effective than manual PjBL in enhancing student creativity. Therefore, the Canva-assisted PjBL model is worthy of recommendation as an alternative learning strategy for creative project-based Pancasila Education in high schools.